Interval analysis to optimise a production line of pharmaceuticals. Issue 2 (1st January 2013) - Kahouadji, Housseyn; Labadi, Karim; Hamaci, Samir; Sari, Zaki
In this paper, we focus on optimisation through simulation of a production line and packaging of pharmaceuticals. Precisely, we propose to couple our simulation model with an optimisation algorithm to determine the optimal number of pallets to insert in the conveyors to maximise the production rate. The idea of the proposed optimisation algorithm is original. It is based on an iterative division of the interval of possible solutions.